A 328 nW, 0.45 V Current Differencing Transconductance Amplifier and Its Application in a Current-Mode Universal Filter - Khateb, Fabian; Kumngern, Montree; Kulej, Tomasz; Vavra, Jiri (My University, 2025)
This paper presents a low-voltage, low-power current differencing transconductance amplifier (CDTA) utilizing the bulk-driven MOS transistor technique in the subthreshold region for reduced voltage and power consumption. The proposed CDTA includes a z-copy terminal, which enhances its functionality in current-mode circuit applications. Designed in the Cadence Virtuoso environment using 0.18 µm CMOS technology from Taiwan Semiconductor Manufacturing Company (TSMC), the amplifier operates with a supply voltage of 0.45 V and consumes 328 nW of power, with a bias current set to 10 nA. The current bandwidth and offset of the CDTA are 35 kHz and 0.3 nA, respectively. To demonstrate its performance, the CDTA is applied in a current-mode universal filter, which can realize low-pass, band-pass, high-pass, band-stop, and all-pass responses within a single topology. This design eliminates issues related to inverting input signals, input signal matching, or the need for multiple input signals. Additionally, the natural frequency of these filtering functions can be electronically controlled. The low-pass filter achieves a dynamic range of 61 dB, with a total harmonic distortion of 0.8%.
Keywords: active filter; bulk-driven MOS transistor; current differencing transconductance amplifier; current-mode circuit